Divided by Terror : American Patriotism after 9/11 - Bodnar, John E., 1944- (The University of North Carolina Press, 2021)
"Americans responded to the deadly terrorist attacks on September 11, 2001, with an outpouring of patriotism, though all were not united in their expression. A war-based patriotism inspired millions of Americans to wave the flag and support a brutal War on Terror in Afghanistan and Iraq, while many other Americans demanded an empathic patriotism that would bear witness to the death and suffering surrounding the attack. Twenty years later, the war still simmers, and both forms of patriotism continue to shape historical understandings of 9/11's legacy and the political life of the nation. John Bodnar's compelling history shifts the focus on America's War on Terror from the battlefield to the arena of political and cultural conflict, revealing how fierce debates over the war are inseparable from debates about the meaning of patriotism itself"--